Tháng Ba 3, 2024

Dùng định nghĩa hai phân thức bằng nhau, chứng minh các đẳng thức sau: a) \(\frac{{{x}^{2}}(2x-1)}{x{{(2x-1)}^{2}}}=\frac{x}{2x-1}\) b) \(\frac{4-x}{x+4}=\frac{{{x}^{2}}-8x+16}{16-{{x}^{2}}}\) c) \(\frac{{{x}^{3}}-9x}{15-5x}=\frac{-x(x+3)}{5}\)

Dùng định nghĩa hai phân thức bằng nhau, chứng minh các đẳng thức sau:

a) \(\frac{{{x}^{2}}(2x-1)}{x{{(2x-1)}^{2}}}=\frac{x}{2x-1}\)

b) \(\frac{4-x}{x+4}=\frac{{{x}^{2}}-8x+16}{16-{{x}^{2}}}\)

c) \(\frac{{{x}^{3}}-9x}{15-5x}=\frac{-x(x+3)}{5}\)

Lời giải chi tiết:

Hướng dẫn giải chi tiết

a) \(\frac{{{x}^{2}}(2x-1)}{x{{(2x-1)}^{2}}}=\frac{x}{2x-1}\)

Ta có:

\(\begin{align} & {{x}^{2}}(2x-1)(2x-1)={{x}^{2}}{{(2x-1)}^{2}} \\ & x{{(2x-1)}^{2}}.x={{x}^{2}}{{(2x-1)}^{2}} \\\end{align}\)

\(\Rightarrow \frac{{{x}^{2}}(2x-1)}{x{{(2x-1)}^{2}}}=\frac{x}{2x-1}\) đúng.

b) \(\frac{4-x}{x+4}=\frac{{{x}^{2}}-8x+16}{16-{{x}^{2}}}\)

Ta có:

\(\begin{align}& (4-x)(16-{{x}^{2}})=(4-x)(4-x)(4+x)=(x+4){{(x-4)}^{2}} \\ & (x+4)({{x}^{2}}-8x+16)=(x+4){{(x-4)}^{2}} \\\end{align}\)

\(\Rightarrow \frac{4-x}{x+4}=\frac{{{x}^{2}}-8x+16}{16-{{x}^{2}}}\) đúng.

c) \(\frac{{{x}^{3}}-9x}{15-5x}=\frac{-x(x+3)}{5}\)

Ta có:

\(\begin{align} & 5({{x}^{3}}-9x)=5x({{x}^{2}}-9)=5x(x+3)(x-3) \\ & -x(x+3)(15-5x)=-5x(x+3)(3-x)=5x(x+3)(x-3) \\\end{align}\)

\(\Rightarrow \frac{{{x}^{3}}-9x}{15-5x}=\frac{-x(x+3)}{5}\) đúng.